Climate change and political participation: Evidence from India - Amrit Amirapu; Irma Clots-Figueras; Juan Pablo Rud (University of Kent, School of Economics, 2022)
Can democratic politics provide a means for responding to climate change? We explore this question by studying the effects of extreme temperatures on Indian elections between 2009 and 2017. We find that areas exposed to extreme temperatures experience an increase in voter turnout and a change in the composition of the pool of candidates who stand for election. As a consequence, electoral outcomes are affected. We provide evidence that the negative effect of climate change on agricultural productivity is the most important driver of our results. In particular, we show that the positive relationship between temperatures and turnout mirrors the negative effect on agricultural productivity and we find that winning candidates are more likely to have an agricultural background. Politicians with an agricultural background invest more on irrigation, which mitigates the effects of high temperatures, both on agricultural production and on turnout. Our paper provides new evidence about the ways in which agents in developing countries (including both voters and candidates) may respond to climate change via political channels.
Keywords: O13; P48; Q54; 330; climate change; political economy; voter turnout